2009
DOI: 10.1111/j.1525-139x.2008.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Reviews: Clinical Implications of Disordered Magnesium Homeostasis in Chronic Renal Failure and Dialysis

Abstract: Magnesium (Mg) is the fourth most abundant cation in the body, mainly located within bone and skeletal muscle. The normal total plasma Mg concentration varies in a narrow range, with approximately 60% present as free Mg ions, the biologically active form. The kidney plays a principal role in Mg balance. Approximately 70-80% of plasma Mg is ultrafilterable, and under normal circumstances, 95% of the filtered load of Mg is reabsorbed. As chronic renal failure (CRF) progresses, urinary Mg excretion may be insuffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
166
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(172 citation statements)
references
References 76 publications
6
166
0
Order By: Relevance
“…Both hyper-and hypomagnesemia have deleterious consequences in CRF patients. Elevated Mg levels are associated with pruritus, and have potentially harmful effects on nerve conduction velocity, osseous metabolism and parathyroid gland function [11]. Various studies found a significant inverse correlation between serum Mg and intact parathyroid hormone (iPTH) levels [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both hyper-and hypomagnesemia have deleterious consequences in CRF patients. Elevated Mg levels are associated with pruritus, and have potentially harmful effects on nerve conduction velocity, osseous metabolism and parathyroid gland function [11]. Various studies found a significant inverse correlation between serum Mg and intact parathyroid hormone (iPTH) levels [10].…”
Section: Introductionmentioning
confidence: 99%
“…Undue suppression of iPTH would result in mineralization defects and adynamic bone disease. Low Mg levels have been associated with impairment of myocardial contractility, intra-dialytic hemodynamic instability, and hypotension [11]. There is also evidence suggesting a significant role for hypomagnesemia in the pathogenesis of cardiovascular diseases in HD patients [12].…”
Section: Introductionmentioning
confidence: 99%
“…44 Clinical studies have also shown protective anticalcification actions of magnesium. 45 In chronic dialysis patients, magnesium carbonate/calcium carbonate, used as a phosphate binder for 18 months, demonstrated a small change in calcium index. 46 Such observations have prompted an interest in using magnesium salts as phosphate binders, not only to treat hyperphosphatemia but also to inhibit development or progression of vascular calcification.…”
Section: Montezano Et Al Vascular Calcification Trpm7 and Magnesiummentioning
confidence: 99%
“…A high supply of dietary magnesium in addition to the additional intake through widely advertised and available supplements may constitute a risk of hypermagnesemia. The excessive intake of oral antacids, laxative and cathartics containing magnesium salts or swallowing of sea water may lead to hypermagnesemia (8)(9)(10).…”
Section: D1scuss]onmentioning
confidence: 99%
“…Concentrated sources of magnesium include antacids, enemas and total parenteral nutrition (5,6). Consequently, the excessive use of preparations containing magnesium salts for medicinal purposes may constitute a health threat (7)(8)(9).…”
mentioning
confidence: 99%